Eusebius of Caesarea's or Eusebius of Emesa's "Theophania"? Evidence from the Lemmata in "Vaticanus Graecus" 1611 - Szesnat, Holger (Vigiliae Christianae, 2019)
This paper is a response to Alice Whealey's proposal concerning the authorship of certain fragments traditionally assigned to Eusebius of Caesarea, arguing that they are more likely the work of his pupil, Eusebius of Emesa. The paper considers the manuscript evidence, specifically the lemmata in Vat.gr. 1611, in relation to the internal evidence considered by Whealey.